Slit-band gastropods (Pleurotomariida) from the Upper Triassic St. Cassian Formation and their diversity dynamics in the Triassic - Karapunar, Baran; Nützel, Alexander (Zootaxa, 2021)
The St. Cassian Formation, Italy, has yielded the most diverse marine invertebrate fauna known from the Triassic. A quarter of all described Triassic gastropod species has been reported from this formation. Most of the gastropod species from the St. Cassian Formation were erected in the 19th century and many of them are known only from their original figures and descriptions. The failure to study type specimens resulted in many erroneous identifications by subsequent authors. Here, we revise the slit band gastropods (Pleurotomariida) from the St. Cassian Formation—one of the major groups present in this formation. A total of 77 nominate Pleurotomariida species belonging to 29 genera and 11 families are present in the St. Cassian Formation which comprises approximately 14 % of the total nominate gastropod species of that formation. In addition, we revise several taxa that had been wrongly assigned to Pleurotomariida. As other gastropod clades, Pleurotomariida experienced a major extinction at the end-Permian mass extinction event. As in the Late Palaeozoic, their relative abundance in gastropod faunas continued to be 30 % in some Anisian faunas but decreased to 5–10 % afterwards. Their diversification at generic level became interrupted by an extinction event within the Carnian, probably by the Carnian Pluvial Event. As a result of their sluggish recovery compared to the other gastropod groups, their species diversity decreased from 26 % during the Permian to 18 % during the Triassic.                Type specimens of the following genera are studied: Proteomphalus, Rhaphistomella, Temnotropis, Kittlidiscus, Stuorella, Schizogonium, Wortheniella, Bandelium, Lancedellia, Rinaldoella, Pseudowortheniella, Paleunema, Ampezzalina, Bandelastraea, Cheilotomona, Pseudoscalites, Delphinulopsis, and Cochlearia.                Nine new pleurotomariidan genera are erected: Amplitomaria, Pseudoananias, Lineacingulum, Pressulasphaera, Cancellotomaria, Acutitomaria, Lineaetomaria, Nodocingulum, and Striacingulum.                Eight new species are described: Schizogonium undae, Acutitomaria kustatscherae, Wortheniella klipsteini, Wortheniella paolofedelei, Rinaldoella tornata, Nodocingulum ernstkittli, Nodocingulum? turris, and Laubella subsulcata.                Eoworthenia frydai is a new replacement name for Worthenia rarissima Barrande.